Treatment of Temporomandibular Joint Ankylosis with Temporalis Superficial Fascia Flap, a case series: - Sohrabi, Maryam; Sezavar, Mehdi; Malekpour, Zahra; Salehi, Mojtaba (Galen Medical Journal, 2013)
Background: Different interpositional materials have been used to prevent recurrence after gap arthroplasty in temporomandibular joint ankylosis. In this study, the temporalis superficial fascia flap was evaluated as an interpositional material after condylectomy. Materials and Methods: 9 Cases of unilateral or bilateral temporomandibular joint ankylosis were evaluated in this study with a follow-up of 12 months. The Al-khayat approach was used as the surgical technique with the inferiorly based temporalis superficial fascia flap. Results: 9 Patients (6 female and 3 male) had a preoperative maximal inter-incisal opening of 3 to 10 mm. During the last follow-up observation after surgery, patients had a maximum inter-incisal opening of 40 to 45 mm. Paresthesia or anesthesia of the temporal branch of facial nerve was absent in all cases. There were no signs of re-ankylosing in any of the patients. Conclusion: The findings of this study showed that the temporalis superficial fascia flap is a good alternative as an interpositional material in treatment of temporomandibular joint ankylosis.